2018
DOI: 10.3390/ijms19113365
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Signaling Pathways Activated by Functional Graphene Nanomaterials

Abstract: The paper reviews the network of cellular signaling pathways activated by Functional Graphene Nanomaterials (FGN) designed as a platform for multi-targeted therapy or scaffold in tissue engineering. Cells communicate with each other through a molecular device called signalosome. It is a transient co-cluster of signal transducers and transmembrane receptors activated following the binding of transmembrane receptors to extracellular signals. Signalosomes are thus efficient and sensitive signal-responding devices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 78 publications
1
27
1
Order By: Relevance
“…In previous studies, some researchers revealed that some graphene derivatives could reduce MMP of the macrophage cell line in a time-and concentrationdependent manner [53,54]. It seems that two important mechanisms are involved in causing damage to mitochondria: (a) direct and physical interactions between nGOs and mitochondrial and/or lysosomal membranes and consequently structural degradation [41] and (b) creating oxidative stress for mitochondrial infrastructures resulting in functional impairment [55,56]. Gurunathan et al [48] and Yuan and Gurunathan [49] revealed that MMP levels reduced after exposure to nGO derivatives.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…In previous studies, some researchers revealed that some graphene derivatives could reduce MMP of the macrophage cell line in a time-and concentrationdependent manner [53,54]. It seems that two important mechanisms are involved in causing damage to mitochondria: (a) direct and physical interactions between nGOs and mitochondrial and/or lysosomal membranes and consequently structural degradation [41] and (b) creating oxidative stress for mitochondrial infrastructures resulting in functional impairment [55,56]. Gurunathan et al [48] and Yuan and Gurunathan [49] revealed that MMP levels reduced after exposure to nGO derivatives.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Generally, literature data demonstrated superior therapeutic performance in cancer chemotherapy experiments, both in vitro and in vivo, due to the improved tissue penetration and cellular uptake of G-based nanocarriers [7,8]. However, the road of G in nanomedicine seems still very long and winding because the current knowledge about the G/cell interactions and the safety issues are not yet sufficiently clarified [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In line with our previous Altogether, the combination of drug carrier ability of MWCNTs with the theranostic properties of porphyrins could allow the development of MWCNTs/TPPS J-aggregates nanohybrids for applications in biomedical field. Unlike from the others families of hybrid carbon nanomaterials [9], the potential applications in biological/pharmaceutical field of carbon based nanomaterials-porphyrins appear still scarcely investigated, especially for J-aggregates self-assemblies as well as their intracellular trafficking, therapeutic and imaging properties. In the literature, it was observed that hybrids nanomaterials based on porphyrinoids [24,63] were prepared at pH different from physiological conditions, and then treated with cells.…”
Section: Discussionmentioning
confidence: 99%